ROLE OF ANTISEPTIC SOLUTION (PYODINE) TO PREVENT INFECTION DURING MESH PLACEMENT - WASEEM, R; GHAYASUDDIN, M; SALMAN, S; JAWAID, B; ERUM, U; SHAKEEL, B (Biological and Clinical Sciences Research Journal, 2024)
Surgical site infections (SSIs) are a significant complication in postoperative care, leading to increased morbidity and healthcare costs. Antiseptic solutions for preoperative skin preparation are crucial in minimising SSIs. Chlorhexidine-alcohol and povidone-iodine solutions are commonly used, but their comparative efficacy in preventing SSIs, especially in mesh replacement surgeries, needs further investigation. Objective: This study aimed to determine the occurrence of surgical site infection (SSI) in wounds after applying povidone-iodine and chlorhexidine-alcohol solutions during mesh replacement surgeries. Methods: This randomised controlled trial was conducted at Kulsoom Bai Valika Hospital, Karachi, from August 1, 2023, to January 31, 2024. Following ethical approval from the institutional review board, 240 patients aged 20-65 undergoing elective surgery were included through non-probability consecutive sampling. Patients allergic to the study solutions or who refused to participate were excluded. Participants were randomly assigned to Group A (chlorhexidine-alcohol, n=120) and Group B (povidone-iodine, n=120). Post-surgery, Group A wounds were scrubbed with chlorhexidine-alcohol and Group B with povidone-iodine. Patients were monitored daily until discharge. Statistical analysis was performed using chi-square tests to compare the incidence of SSIs between the groups. Results: The mean age of participants was 41.32±11.6 years in Group A and 41.62±11.5 years in Group B. Within a 30-day follow-up, SSIs were observed in 23% of Group A and 40% of Group B (p<0.0001). Superficial incisional infections were 16% in Group A and 28% in Group B (p<0.0001). Deep incisional infections were 6% in Group A and 13% in Group B (p=0.004). Conclusion: The use of chlorhexidine-alcohol for antisepsis in mesh replacement surgeries significantly reduced the incidence of surgical site infections compared to povidone-iodine-alcohol. This suggests that chlorhexidine-alcohol is a more effective antiseptic solution for preventing SSIs in such procedures.